E-062 Intracranial Stenting for Atherosclerotic Disease with Aggressive Anti-platelet Therapy Management: A Consecutive Series of 154 Patients. (26th July 2014) - Alexander, M; Nuno, M; Alexander, J; Agutos, C; Yu, W
Abstract : Introduction: Contemporary studies of intracranial stenting have utilised standard or aggressive medical therapy involving dual anti-platelet therapy, but have not evaluated anti-platelet therapy resistance as a component of treatment failure. Methods: The current study evaluates a prospective aggressive anti-platelet therapy management approach at two institutions in a consecutive series of 154 patients with symptomatic intracranial atherosclerotic disease (ICAD) treated with angioplasty and stenting with the Wingspan self-expanding nitinol stent. Anti-platelet medication therapeutic effects of aspirin and clopidogrel were measured prior to the procedures by platelet function assay, thromboelastography, aggregometry, or Accumetrics VerifyNow systems. Medications were adjusted or changed for subtherapeutic or supratherapeutic values with clopidogrel goal inhibition of 20–80% and aspirin reactive unit (ARU) less than 550. Results: A total of 154 patients with symptomatic ICAD were treated from 2005 to 2014. The periprocedural complication rate was 3.9% (6/154) with 1 subarachnoid haemorrhage, 0 intraparenchymal haemorrhages, 5 perforator strokes, and no stent thrombosis. With a mean follow up of 2.3 years, the total ipsilateral stroke and death rate was 6.5% (10/154). The relative aspirin resistance rate was 7.8% and the relative clopidogrel resistance rate was 14.9% in this series. Eight of the patients (5.2%) required repeat angioplasty for symptomatic re-stenosis within the first year. The mean time to treatment was 10.7 days following the last stroke. Conclusions: With aggressive monitoring and management of anti-platelet medications, intracranial stenting complications of stent thrombosis and distal emboli can be reduced, although there is still a significant risk of perforator strokes, particularly in the middle cerebral artery and basilar distributions. Disclosures: M. Alexander: 1; C; Stryker Neurovascular. M. Nuno: None. J. Alexander: None. C. Agutos: None. W. Yu: 1; C; Stryker Neurovascular.